2016
DOI: 10.1016/j.ijdevneu.2016.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Reduced endogenous urinary total antioxidant power and its relation of plasma antioxidant activity of superoxide dismutase in individuals with autism spectrum disorder

Abstract: Individuals with autism spectrum disorders (ASD) have impaired detoxification capacity. Investigating the neurobiological bases of impaired antioxidant capacity is thus a research priority in the pathophysiology of ASD. We measured the urinary levels of hexanoyl-lysine (HEL) which is a new oxidative stress biomarker, total antioxidant power (TAP) and DNA methylation biomarker 8-hydroxy-2'-deoxyguanosine (8-OHdG), and the plasma levels of superoxide dismutase (SOD), which is a major antioxidant enzyme. We exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 80 publications
(101 reference statements)
0
4
0
Order By: Relevance
“…The superior performance of the SVM using a radial kernel function indicates that individuals with ASD might have levels of 8-OH-dG below or above an optimal range [46,47], rather than simply levels that are higher than neurotypical individuals. This could explain some the disparate findings of previous studies, among which some have found increased levels of 8-OH-dG in individuals with ASD [12,48,49], while others have not [35,36,50]. In individuals with ASD, such deviations from an optimal level of 8-OH-dG could be a reflection of a departure from an appropriate range of ROS expression, which has been shown to be important in regulating neuronal differentiation, migration [51,52], and synaptic pruning [53,54], which are all processes thought to be involved in the etiology of ASD [55,56].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The superior performance of the SVM using a radial kernel function indicates that individuals with ASD might have levels of 8-OH-dG below or above an optimal range [46,47], rather than simply levels that are higher than neurotypical individuals. This could explain some the disparate findings of previous studies, among which some have found increased levels of 8-OH-dG in individuals with ASD [12,48,49], while others have not [35,36,50]. In individuals with ASD, such deviations from an optimal level of 8-OH-dG could be a reflection of a departure from an appropriate range of ROS expression, which has been shown to be important in regulating neuronal differentiation, migration [51,52], and synaptic pruning [53,54], which are all processes thought to be involved in the etiology of ASD [55,56].…”
Section: Discussionmentioning
confidence: 83%
“…HEL can be a useful biomarker for initial stages of lipid peroxidation [34]. Urinary levels of HEL were also found to be elevated in children with ASD [35], with a recent study by Yui et al showing that increased HEL is associated with decreased antioxidant capacity in children with ASD [36].…”
Section: Introductionmentioning
confidence: 99%
“… 12 , 20 The excreted antioxidants are lower in autistic patients compared with healthy age-matching subjects and upon correlation with severity of the disease, such as superoxide dismutase. 21 , 22 Also, ceruloplasmin and transferrin antioxidants show suboptimal levels in serum of autistic children, leading to abnormal metabolism of toxic and oxidative stress–mediating metal ions. 23 Recent genetic studies have identified variants of some antioxidant enzyme-coding genes that increase the susceptibility to autism.…”
Section: Introductionmentioning
confidence: 99%
“…In a study in which 68 children diagnosed with ASD were compared with 54 healthy controls, 8-OHdG levels in peripheral lymphocyte DNA were found to be significantly higher in the ASD group [20]. However, in other studies no significant difference was found between autism and healthy control groups in terms of urinary 8-OHdG levels [38,39]. In the present study, when 8-OHdG values were compared between the ASD and control groups, the 8-OHdG value was found to be significantly higher in ASD patients.…”
Section: Discussionmentioning
confidence: 96%